2019
DOI: 10.1021/acsearthspacechem.8b00157
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Hydrous Aluminosilicate Melts at High Pressures

Abstract: In this study, we use first-principles molecular dynamics simulations to explore the behavior of anhydrous aluminosilicate melt with a stoichiometry of NaAlSi2O6 up to pressures of ∼30 GPa and temperatures between 2500 and 4000 K. We also examine the effect of water (∼4 wt % H2O) on the equation of state and transport properties of the aluminosilicate melt and relate them to atomistic scale changes in the melt structure. Our results show that water reduces the density and bulk modulus of the anhydrous melt. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 99 publications
(229 reference statements)
10
31
0
Order By: Relevance
“…The high-pressure densities determined in this study are consistent with the room-pressure density calculated from the ideal mixing model using partial molar volumes of the oxide components [54]. Figure 4 compares our results with previous studies on jadeite melt including X-ray absorption measurements from Sakamaki [33], FPMD simulations from Bajgain et al [38], and classical molecular dynamics (MD) simulations from Suzuki et al [21]. After correcting for thermal effects, our data are mostly consistent with the results from the FPMD [38] over the entire pressure range of our experiments.…”
Section: Density Of Jadeite Melt At High Pressuressupporting
confidence: 89%
See 4 more Smart Citations
“…The high-pressure densities determined in this study are consistent with the room-pressure density calculated from the ideal mixing model using partial molar volumes of the oxide components [54]. Figure 4 compares our results with previous studies on jadeite melt including X-ray absorption measurements from Sakamaki [33], FPMD simulations from Bajgain et al [38], and classical molecular dynamics (MD) simulations from Suzuki et al [21]. After correcting for thermal effects, our data are mostly consistent with the results from the FPMD [38] over the entire pressure range of our experiments.…”
Section: Density Of Jadeite Melt At High Pressuressupporting
confidence: 89%
“…Figure 4 compares our results with previous studies on jadeite melt including X-ray absorption measurements from Sakamaki [33], FPMD simulations from Bajgain et al [38], and classical molecular dynamics (MD) simulations from Suzuki et al [21]. After correcting for thermal effects, our data are mostly consistent with the results from the FPMD [38] over the entire pressure range of our experiments. Although our results also agree with those of classical MD simulations from Suzuki et al [21] between~1-3 GPa, a deviation in the pressure effects on density can be observed.…”
Section: Density Of Jadeite Melt At High Pressuressupporting
confidence: 86%
See 3 more Smart Citations